Functional lymphatic reserve capacity is depressed in patients with a Fontan circulation. Issue 11 (31st May 2021) - Mohanakumar, Sheyanth; Kelly, Benjamin; Turquetto, Aida Luiza Ribeiro; Alstrup, Mathias; Amato, Luciana Patrick; Barnabe, Milena Schiezari Ru; Silveira, João Bruno Dias; Amaral, Fernando; Manso, Paulo Henrique; Jatene, Marcelo Biscegli; Hjortdal, Vibeke Elisabeth
Abstract: Background: Lymphatic abnormalities play a role in effusions in individuals with a Fontan circulation. Recent results using near‐infrared fluorescence imaging disclosed an increased contraction frequency of lymphatic vessels in Fontan patients compared to healthy controls. It is proposed that the elevated lymphatic pumping seen in the Fontan patients is necessary to maintain habitual interstitial fluid balance. Hyperthermia has previously been used as a tool for lymphatic stress test. By increasing fluid filtration in the capillary bed, the lymphatic workload and contraction frequency are increased accordingly. Using near‐infrared fluorescence imaging, the lymphatic functional reserve capacity in Fontan patients were explored with a lymphatic stress test. Methods: Fontan patients ( n = 33) were compared to a group of 15 healthy individuals of equal age, weight, and gender. The function of the superficial lymphatic vessels in the lower leg during rest and after inducing hyperthermia was investigated, using near‐infrared fluorescence imaging. Results: Baseline values in the Fontan patients showed a 57% higher contraction frequency compared to the healthy controls (0.4 ± 0.3 min −1 vs. 0.3 ± 0.2 min −1, p = 0.0445). After inducing stress on the lymphatic vessels with hyperthermia the ability to increase contraction frequency was decreased in the Fontan patients compared to the controls (0.6 ± 0.5 min −1 vs. 1.2 ± 0.8 min −1, p = 0.0102). Conclusions: Fontan patients had a higher lymphatic contraction frequency during normal circumstances. In the Fontan patients, the hyperthermia response is dampened indicating that the functional lymphatic reserve capacity is depressed. This diminished reserve capacity could be part of the explanation as to why some Fontan patients develop late‐onset lymphatic complications. Abstract : We report, for the first time, that the functional lymphatic reserve capacity is depressed in patients with a Fontan circulation. Using Near‐Infrared Fluorescence imaging to asses function and morphology of the peripheral lymphatic vessels in patients with subclinical and clinical symptoms of effusions, we have introduced a new simple way to stress the lymphatic vessels to reveal lymphatic functional capacity.